Genome-wide identification of Glycyrrhiza uralensis Fisch. MAPK gene family and expression analysis under salt stress relieved by Bacillus subtilis - Gao, Pengchao; Xiao, Jiancai; Guo, Wanying; Fan, Rui; Zhang, Yan; Nan, Tiegui (Frontiers in Genetics, 2024)
Introduction: Research on Glycyrrhiza uralensis, a nonhalophyte that thrives in saline–alkaline soil and a traditional Chinese medicinal component, is focused on improving its ability to tolerate salt stress to increase its productivity and preserve its “Dao-di” characteristics. Furthermore, the inoculation of bioagents such as Bacillus subtilis to increase plant responses to abiotic stressors is currently a mainstream strategy. Mitogen-activated protein kinase (MAPK), a highly conserved protein kinase, plays a significant role in plant responses to various abiotic stress pathways. Methods: This investigation involved the identification of 21 members of the GuMAPK family from the genome of G. uralensis, with an analysis of their protein conserved domains, gene structures, evolutionary relationships, and phosphorylation sites using bioinformatics tools. Results: Systematic evolutionary analysis of the 21 GuMAPKs classified them into four distinct subgroups, revealing significant differences in gene structure and exon numbers. Collinearity analysis highlighted the crucial role of segmental duplication in expanding the GuMAPK gene family, which is particularly evident in G. uralensis and shows a close phylogenetic relationship with Arabidopsis thaliana, tomato, and cucumber. Additionally, the identification of phosphorylation sites suggests a strong correlation between GuMAPK and various physiological processes, including hormonal responses, stress resistance, and growth and development. Protein interaction analysis further supported the role of GuMAPK proteins in regulating essential downstream genes. Through examination of transcriptome expression patterns, GuMAPK16-2 emerged as a prospective pivotal regulatory factor in the context of salt stress and B. subtilis inoculation, a finding supported by its subcellular localization within the nucleus. Discussion: These discoveries offer compelling evidence for the involvement of GuMAPK in the salt stress response and for the exploration of the mechanisms underlying B. subtilis’ enhancement of salt tolerance in G. uralensis.